Optimizing Duolingo Application Usage to Improve Language Skills Among University Students - Margaret Stevani (PT. Global Research Collaboration, 2024)
This community service implementation explores the optimization of Duolingo application usage to enhance language skills among university students. The study investigates the effectiveness of incorporating Duolingo into the language learning curriculum and its impact on students' listening, speaking, reading, and writing abilities. The community service on aims to assess the application's role in fostering a more engaging and interactive language learning experience. The study anticipates identifying the specific language skills that show improvement and gauging the overall satisfaction and motivation of students in utilizing Duolingo. In the implementation of this community service, utilized online methods through Zoom meetings to provide flexibility in terms of space and time, allowing greater accessibility for participating students.The findings aim to provide insights into the potential of leveraging technology, particularly the Duolingo application, as a supplementary tool for language education in a university setting. The conclusion a contribution to the ongoing discourse on innovative language teaching methods and their impact on the academic performance and language proficiency of university students